INCREASING INNOVATION AND HYGIENE OF CULINARY OFFERINGS IN THE IMPLEMENTATION OF TOURISM DESTINATION ACTIVITIES IN BOGOR REGENCY - Rahmaniyah Utami, Nisa; Hariani, Dina (LPPM Univ. Ibn Khaldun Bogor, 2023)
The Bogor district government is aggressively increasing the need for workers in the tourism sector. One of the activities is by providing training to tourism sector workers in the Bogor district. This activity was sourced from the Republic of Indonesia's Non-Physical Special Allocation Fund (DAK) for the 2022 Fiscal Year. The Bogor Regency Culture and Tourism Office held Training on Increasing Innovation and Hygiene Culinary Serving in Tourism Destinations at Taman Bukit Palem Resort, Pancawati, Bogor Regency. The training participants consisted of 36 participants who worked in the tourism sector such as cafes, hotels, restaurants, and resorts in the Bogor district. The implementation of these activities is in the form of training on creativity and innovation by involving the participation of tourism sector workers.